VLP‐factory™ and ADDomer©: Self‐assembling Virus‐Like Particle (VLP) Technologies for Multiple Protein and Peptide Epitope Display. Issue 3 (17th March 2021) - Sari‐Ak, Duygu; Bufton, Joshua; Gupta, Kapil; Garzoni, Frederic; Fitzgerald, Daniel; Schaffitzel, Christiane; Berger, Imre
Abstract: Virus‐like particles (VLPs) play a prominent role in vaccination as safe and highly versatile alternatives to attenuated or inactivated viruses or subunit vaccines. We present here two innovations, VLP‐factory™ and ADDomer ©, for creating VLPs displaying entire proteins or peptide epitopes as antigens, respectively, to enable efficient vaccination. For producing these VLPs, we use MultiBac, a baculovirus expression vector system (BEVS) that we developed for producing complex protein biologics in insect cells transfected with an engineered baculovirus. VLPs are protein assemblies that share features with viruses but are devoid of genetic material, and thus considered safe. VLP‐factory™ represents a customized MultiBac baculovirus tailored to produce enveloped VLPs based on the M1 capsid protein of influenza virus. We apply VLP‐factory™ to create an array of influenza‐derived VLPs presenting functional mutant influenza hemagglutinin (HA) glycoprotein variants. Moreover, we describe MultiBac‐based production of ADDomer ©, a synthetic self‐assembling adenovirus‐derived protein‐based VLP platform designed to display multiple copies of pathogenic epitopes at the same time on one particle for highly efficient vaccination. © 2021 The Authors. Basic Protocol 1 : VLP‐factory™ baculoviral genome generation Basic Protocol 2 : Influenza VLP array generation using VLP‐factory™ Basic Protocol 3 : Influenza VLP purification Basic Protocol 4 : ADDomer © BioBrick design, expression, and purification Basic Protocol 5 : ADDomer © candidate vaccines against infectious diseases